RELATIONSHIP BETWEEN RENAL STONE LOCATION WITH STONE-FREE RATE AFTER ESWL - Siregar, Laudeo Dhanaba; Warli, Syah Mirsya (Indonesian Urological Association, 2017)
Objective: This study aims to evaluate the relationship between stone location and stone location in kidney stone to the stone-free rate after Extracorporeal Shock Wave Lithotripsy (ESWL) procedure. Material & method: This is a non-experimental research using descriptive analytic method with retrospective study design that takes data from patient medical record diagnosis of urinary tract stones and ESWL action from January 2011 until December 2013 in the Department of Surgery Division of Urology General Hospital H. Adam Malik, Medan. Results: It was found that if the size of the stone only is the only factor that counts in patients who get a urinary tract stones ESWL therapy, it is not found a statistically significant relationship. Stone location plays an important role in the incidence of stone-free patients with urinary tract stones ESWL therapy. Conclusion: ESWL therapeutic efficacy in the treatment of patients with kidney stones is not only determined by the size and location of the stone, but is also determined by the number of stones, stone composition, frequency ESWL is used, and the thickness of the skin of the patient.